STUDY TENTANG PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 WONOAYU SIDOARJO - MAY BERLIN (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Based on observations on the importance of quality learning materials, and the notion that accounting is a pretty difficult subjects, this is the background behind the author to conduct research on the use of teaching material accounting in high school Wonoayu Sidoarjo of 1. This research is descriptive research with research subjects accounting teacher in high school Wonoayu Sidoarjo land 1, whereas the research objects of learning materials that are used in accounting class lesson XI. Data analysis techniques used in this research is a descriptive percentage analysis techniques. Results of this study indicate that the teaching material used in high school Wonoayu Sidoarjo of 1 is teaching material with the type of module and text books. Teaching material with the type of module in high school Wonoayu Sidoarjo of 1was assessed based on the results of the feasibility to two expert study with 69.87%, decent criteria, while the percentage of teaching material with the kind of text book based on the study of two experts to obtain the percentage of 77.33% with very decent criteria. Keywords : Teaching Material